Psycholinguistic profiles of proficient and struggling readers in relation to reading fluency - Naina Mohamed Mohamed Safeek,; Kway, Eng Hock (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research delves into the psycholinguistic profiles of proficient and struggling readers among junior secondary Tamil students in Sri Lanka, with the aim of enhancing literacy instruction and intervention. Grounded in the Simple View of Reading (SVR) Theory, the study explores distinct psycholinguistic profiles and predictive factors for reading success or challenges. The research involves 140 carefully chosen students; 70 struggling readers and 70 good readers were identified based on their performance in the national Grade 5 Scholarship exam of 2021 in Puttalam South Divisional Education. A psycholinguistic screening test (PST) aligning with the SVR framework was employed to evaluate decoding and linguistic comprehension skills. The data analysis reveals notable disparities in decoding and linguistic comprehension skills between proficient and struggling readers. Linear regression analysis yields a robust model, elucidating a substantial portion of the variance in the PST profiles and reinforcing the influence of psycholinguistic profiles on reading fluency. The findings substantiate the existence of distinctive reader profiles, underscoring the significance of decoding and linguistic comprehension skills. Proficient readers excel across multiple components, while struggling readers may grapple with deficits in both decoding and linguistic comprehension. The interplay between these skills and reading comprehension is complex and dependent on reading proficiency. This study emphasizes decoding and comprehension in reading fluency development. It enhances understanding of reading dynamics, with broader implications for literacy education, transcending Sri Lanka's borders.